IstirÄtijiyah Al-Taâ€™allum Al-Lugah Al-Arabiyyah li Al-NÄá¹iqÄ«na bi Gair Al-Arabiyyah li Taá¹wÄ«r MahÄrah Al-KalÄm li á¹¬ullÄb Gair Al-Suâ€™Å«diyyin fi BarnÄmij Al-Mukaá¹¡á¹¡af Qism Al-Lugah wa Al-á¹ aqÄfah Maâ€™had Al-LugawiyyÄt Al-Arabiyyah: bi JÄmiah Al-Mulk Saud Al-RiyÄá¸ Al-Mamlakah Al-Arabiyyah Al-Suâ€™Å«diyyah - Muhammad Ainul Yaqin (Arabic Education Program IAIN Pekalongan, 2020)
Strategy in teaching the Arabic language to non-Arabic speakers is an important aspect in that it can help students achieve their learning goals and develop their skills, especially speaking skills. In this case, teachers or lecturers must prepare teaching strategies so that instructional activities become more interesting and innovative. Speaking skills are one of the four language skills and crucial skills for communication. This study aims to uncover the strategies used in teaching Arabic to non-Arabic speakers, especially to develop speaking skills at intensive Arabic events organized by the Department of Language and Culture, the Faculty of Arabic Language, King Saud University of Riyadh. This qualitative research is a case study type. Data of the research were collected through observation, interviews, and documentation from students of the first and second levels. The results of this study show that, at the first level, the lecturers used face-to-face, discussion, and conversation strategies, whereas, at the second level, the lecturers used face-to-face by giving the title of the material to be used in the conversation. During the instructional activities, a book titled